Structural and Histochemical Alterations in the Aortic Valves of Elderly Patients: A Comparative Study of Aortic Stenosis, Aortic Regurgitation, and Normal Valves. (25th September 2016) - Miura, Katsutoshi; Katoh, Hideki
Abstract : The aim of this study was to reveal the pathogenesis of aortic stenosis (AS) and regurgitation (AR) by comparing differences in mechanical and biochemical alterations. We applied scanning acoustic microscopy (SAM) to measure the speed of sound (SOS) through valves to estimate the elasticity and monitor sensitivity to protease treatment, as the SOS is correlated with the stiffness of materials, which is reduced after digestion by proteases. The fibrosa of both the AS and AR groups were stiffer than the fibrosa of the normal group. The AR group displayed significantly stiffer fibrosa than the AS group, with the exception of calcified areas. The AS group showed significantly decreased SOS values following protease digestion, whereas the AR showed little reduction. The AS group presented type III collagen in the fibrosa and the ventricularis. In the AR group, both type I collagen and type III collagen coexisted in the fibrosa and the ventricularis. Upon immunostaining for advanced glycation end-products, the AS group showed sparse, weak staining, whereas the AR group presented a strong, band-like positive reaction in the fibrosa. In conclusion, tissue remodelling associated with damage and repair is associated with AS pathogenesis, whereas static chemical alterations with slow collagen turnover induce AR.